Йов Кондзелевич: ієромонах і геніальний митець - Ларіонова, В.; Борисович, Л. (Інститут народознавства НАН України, 2007)
Hiob Kondzelevych creative work is unique artistic phenomenon. It is specified by high uniting of Eastern and Western traditions of icon-painting. The peak of his creativeness is presented by iconostasis of the temple at Maniava (Bohorodchany) hermitary, painted at 1609-1705. In artistic heritage one might see great number of innivative artistic approaches, characteristic for Mannerism style. After a time those had influence upon the development of Ukrainian painting at XVII c.